2020
DOI: 10.1186/s13011-020-0254-x
|View full text |Cite
|
Sign up to set email alerts
|

“Becoming myself”: how participants in a longitudinal substance use disorder recovery study experienced receiving continuous feedback on their results

Abstract: Background: Being a participant in longitudinal follow-up studies is not commonly a factor considered when investigating useful self-change aspects for individuals attempting recovery from substance use disorder (SUD). This study reports on how ongoing monitoring, and feedback on data results in a longitudinal follow-up study of SUD recovery were perceived by individuals who had achieved long-term abstinence and social recovery. Methods: Interviewers with first-hand experience with the topic conducted intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…10 We have also explored their experiences of how close relationships may have impacted recovery, 11 their perceived benefits of drug use, 12 and how ongoing monitoring and feedback on the data results in a longitudinal follow-up study on SUD recovery were described. 13 Now, we examine the parts of this material that focus on the role of meaningful activities. In doing so, we have approached these activities in a broad sense and included both work and leisure, as both are found to be associated with important health benefits for people with an SUD.…”
Section: Introductionmentioning
confidence: 99%
“…10 We have also explored their experiences of how close relationships may have impacted recovery, 11 their perceived benefits of drug use, 12 and how ongoing monitoring and feedback on the data results in a longitudinal follow-up study on SUD recovery were described. 13 Now, we examine the parts of this material that focus on the role of meaningful activities. In doing so, we have approached these activities in a broad sense and included both work and leisure, as both are found to be associated with important health benefits for people with an SUD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we added motivational strategies, such as early establishment of working alliances, to facilitate cooperation and adapted the study protocol to the individual needs of each participant [48]. We have previously explored participants' experiences of receiving continuous feedback on their results [47], emphasizing the function of feedback and short messaging service (SMS) as important reminders of the importance of long-term efforts and comprehensive self-change in recovery processes.…”
Section: The Present Studymentioning
confidence: 99%
“…The annual assessment used 14 instruments and self-report forms (see ''Appendix''). We used organizational and motivational strategies to enhance retention rates in the Stayer study, such as reminders of appointments, flexible visiting characteristics [48], and access to data on request [47].…”
Section: The Stayer Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinell and Barfoed (2014) states that the ASI tool is important for, and has the ability to affect, the interaction between social worker and client (Martinell Barfoed 2014). Further, research on clients' perspective have shown that monitoring (Scott et al, 2005) and continuous feedback, which regular assessments provide, can help motivate client progress and contribute to recovery (Svendsen et al 2020).…”
Section: Practice-related Researchmentioning
confidence: 99%